Risk assessment framework: application of Bayesian Belief Networks in an ammunition delaboration project - Malbašić, Slobodan B.; Đurić, Stefan V. (Vojnotehnički glasnik / Military Technical Courier, 2019)
Models that represent real problems have been relying so far on historical data to draw upon conclusions. One negative aspect of these models was that they could not predict future states based on real data instantly collected or new sources of risk that suddenly appeared. To overcome this problem, this work presents the process of building a realistic predictive model using Bayesian Belief Networks (BBNs) and the AgenaRisk software. BBNs are a direct representation of real problems where their graphical structure represents real causal connections and not just a flow of information. Software tools providing algorithms for dealing with conditional probabilities have been developed. The Bayesian Theorem, a theoretical background for conditional probability, was also explained in the paper. Another benefit of using BBNs is that the reasoning process can operate by propagating information in any direction (top-down or bottom-up) which makes it a powerful tool in risk assessment and a decision-making process. The paper also provides the core principles and the power of BBNs and their application in the project planning phase for ammunition delaboration (resolving problems of surplus and obsolete ammunition in stockpiles), where risk assessment is one of the required processes which helps in making a final decision for project approval or not. The sensitivity and SWOT analyses are also performed as valuable and helpful tools for validation and making conclusions.
Keywords: conditional probability; Bayesian Belief Networks; risk assessment; sensitivity analysis; SWOT analysis